The application of activity-based costing and activity-based planning influences decision making / Hussein Mubark Salim Dhubea and Saleh Ahmed Al-Riami - Dhubea, Hussein Mubark Salim; Al-Riami, Saleh Ahmed (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2017)
This study provides information on the efficiency of decision making based on accurate information through the use activity-based costing (ABC) and activity based planning (APB). The results of this study provide additional insights for the management to adopt future strategic planning by controlling costs and invest in profitable projects. Furthermore, the results of the study will be helpful for all decision makers at all levels of the company. The findings of this study can contribute to the literature review.